Prevalence, intensity and associated morbidity of Schistosoma japonicum infection in the Dongting Lake region, China - Julie Balen; Zheng-Yuan Zhao; Gail M Williams; Donald P McManus; Giovanna Raso; Jürg Utzinger; Jie Zhou; Yue-Sheng Li (The World Health Organization, 2007)
OBJECTIVE: To determine the prevalence and intensity of Schistosoma japonicum infection and associated morbidity, and to estimate the infected human and buffalo populations in the Dongting Lake region, Hunan province, China. METHODS: We used data from the third national schistosomiasis periodic epidemiological survey (PES) of 2004. These included 47 144 human serological and 7205 stool examinations, 3893 clinical examinations and questionnaire surveys, and 874 buffalo stool examinations, carried out in 47 villages in Hunan province. Serological examinations were performed using the enzyme linked immunosorbent assay technique and human stool samples were examined by the Kato-Katz method. Stools from buffaloes and other domestic animals were examined for schistosome infection by the miracidial hatching test. FINDINGS: Sero-prevalence was 11.9% (range: 1.3-34.9% at the village level), and the rate of egg-positive stools was estimated at 1.9% (0-10.9%) for the same population. The prevalence of infection among buffaloes was 9.5% (0-66.7%). Extrapolating to the entire population of the Dongting Lake region, an estimated 73 225 people and 13 973 buffaloes were infected. Most frequently reported symptoms were abdominal pain (6.2%) and bloody stools (2.7%). More than half of the clinically examined people reported having had at least one prior antischistosomal treatment. CONCLUSION: There was a significant reduction in the number of humans infected with S. japonicum since the previous national PES carried out in 1995, partially explained by large-scale chemotherapy campaigns. However, a near-stable number of buffalo infections suggest continuing human re-infection, which may lead to future increases in human prevalence.